The competent authority : a novel - Chowdhury, Shovon
A couple of decades from now, India is not shining the Chinese have nuked large parts of the country; Bombay has been obliterated; Delhi is in the throes of rigorous reconstruction; Bengal has seceded and is now a protectorate of China; the Maoists have taken over much of what remains. The southern states are a distant and tranquil place that nobody has visited in years. The most powerful person in the country is a deranged bureaucrat called the Competent Authority, who has used his official position as the head of the Bureau of Reconstruction, to subvert all forces of governmental authority. Cloaked in anonymity, his identity known only to his terrified minions, the CA rules the remnants of India with an iron fist. Although, in theory, the government and the armed forces still exist, the Prime Minister, who looks very familiar, and the General, who commands the Army, are mere puppets in the hands of the Competent Authority. All they can do is watch in horror as he tries to put in motion a fiendish plan to annihilate everyone in the country, for reasons that are completely logical. The only person who can stop him is Pintoo, a mutant twelve year old from Shanti Nagar, where all the poor people live. Determined to thwart the CAs plan and save the country from disaster, Pintoo employs three reluctant henchmen to help him: Pande, a corrupt and vicious policeman, Chatterjee, a pessimistic but determined CBI officer and Ali, the last surviving member of Al Qaeda. And then theres also the matter of the hand that has a mind of its own.